Upaya Peningkatan Pemahaman Moderasi Beragama Masyarakat Kecamatan Bengkalis - Riki Astafi; Wira Sugiarto; Wan Muhammad Fariq (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The efforts to enhance the understanding of religious moderation in the Bengkalis District aim to strengthen tolerance and social harmony in a diverse society. This community service program is designed to provide education and outreach on the values of religious moderation, such as tolerance, respect, and rejection of extremism. The approach used in this program includes seminars, workshops, and interactive discussions involving various elements of the community, including religious leaders, youth, and local communities. Active participation from different parties is expected to increase the effectiveness of conveying the messages of moderation. The evaluation shows a significant improvement in the community's understanding and attitudes regarding religious moderation. Not only has awareness increased, but the program has also successfully fostered mutual respect among different religious groups. This improvement is reflected in the following indicators: Inclusive and Tolerant Attitudes increased from 40% to 75%, Neutral Attitudes decreased from 35% to 20%, and Exclusive and Intolerant Attitudes dropped from 25% to 5%. Thus, this initiative not only provides short-term positive impacts but also has the potential to become a model for implementing similar programs in other areas. These efforts are expected to contribute to the creation of a more harmonious, tolerant society that can coexist in diversity. The program emphasizes the importance of interfaith dialogue as a foundation for inclusive and peaceful social development, which in turn supports sustainable national development. This program reflects a structured and holistic strategy in promoting religious moderation and building a cohesive society.